“I Thank My Lucky Star for the Time spent with my Family”: Efforts to Reunite with Families among Members of the Great Emigration - Zajac, Oliver (Acta Poloniae Historica, 2024)
The present text brings to light the social and political challenges of reuniting with families among members of the Great Emigration and the intricate question of the possibility of travel and permanent or partial return from emigration. These questions are examined through two case studies: that of Władysław Zamoyski and his three attempts at a short-term reunion with his family, and that of Józef Głębocki and his struggles to obtain a one-year return to Austrian Galicia. The main focus of the analysis is the communication between the emigrants, their family members, and representatives of the Austrian Empire. Despite many differences, the same elements can be found in both cases, such as the emphasis on the emotional difficulty of emigration for the emigrants and their families and the desire to be reunited with elderly and sick parents. Declarations of non-political purposes of the return to Austria and financial guarantees of material assets of the émigrés are mentioned as arguments for their cases. At the same time, the analysed cases also shed light on the societal and political challenges faced by the emigrants when communicating with Austrian authorities and the problem of the long-term consequences of the partitions of the Polish-Lithuanian Commonwealth.